Application of Discrete Mathematical Model in Edge Distortion Correction of Moving Image - Qingwei Xu; Zhoufeng Liu (Discrete Dynamics in Nature and Society)
The existing edge distortion correction methods of moving images ignore the consistency of human subjective vision in the restoration process. Therefore, this study proposes an edge distortion correction method of moving images using a discrete mathematical model. According to the image binarization, the moving target region is segmented, the motion fuzzy degradation model is constructed by using the discrete mathematical model, the global structure information of the image is considered by the structure similarity, the image gradient is transformed from the rectangular coordinate system to the polar coordinate system, the image deconvolution algorithm of the edge distribution of the natural image is used to enhance the image edge features, and the edge distortion correction of the moving image is realized. The experimental results show that the astringency of the experimental scattergram is obviously improved, the fitting line is almost a straight line, and it has good recognition of the jump of the gray level of noise points, which can meet the requirements of the consistency of the subjective vision of human eyes.